2016
DOI: 10.1016/j.leukres.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cell death in FLT3-ITD positive acute myeloid leukemia by combined treatment with metformin and 6-benzylthioinosine

Abstract: Current therapy for acute myeloid leukemia (AML) primarily includes high-dose cytotoxic chemotherapy with or without allogeneic stem cell transplantation. Targeting unique cellular metabolism of cancer cells is a potentially less toxic approach. Monotherapy with mitochondrial inhibitors like metformin have met with limited success since escape mechanisms such as increased glycolytic ATP production, especially in hyperglycemia, can overcome the metabolic blockade. As an alternative strategy for metformin therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…As a consequence metformin was shown to synergize with the non-metabolizable glucose analog and hexokinase inhibitor 2-deoxy-glucose (2-DG) in T-ALL ( 80 ) and in CML ( 99 ) and with the glycolysis inhibitor sodium dichloroacetate (DCA) in B-CLL ( 100 ). Similar effects have been observed in Flt3-positive AML when metformin was associated with the metabolic inhibitor 6-BT ( 101 ). Cell death induction of MM cells after disrupting protein homeostasis with the proteasome inhibitor bortezomib can be enhanced by metformin, preventing a protective autophagic response ( 102 ).…”
Section: Leukemiasupporting
confidence: 73%
“…As a consequence metformin was shown to synergize with the non-metabolizable glucose analog and hexokinase inhibitor 2-deoxy-glucose (2-DG) in T-ALL ( 80 ) and in CML ( 99 ) and with the glycolysis inhibitor sodium dichloroacetate (DCA) in B-CLL ( 100 ). Similar effects have been observed in Flt3-positive AML when metformin was associated with the metabolic inhibitor 6-BT ( 101 ). Cell death induction of MM cells after disrupting protein homeostasis with the proteasome inhibitor bortezomib can be enhanced by metformin, preventing a protective autophagic response ( 102 ).…”
Section: Leukemiasupporting
confidence: 73%
“…NOX2 inhibitor disabled mitochondrial transfer, increased AML cell apoptosis and improved survival of xenograft mice (Marlein et al , ). A synergy was observed between metformin, which inhibits Complex I in mitochondria, and the broad‐spectrum metabolic inhibitor 6‐benzylthioinosine (6‐BT), with reduced glycolysis, ROS suppression and increased apoptosis (Sabnis et al , ). Inhibition of HIF1α by 2‐methoxyestradiol was found to activate the mitochondrial apoptotic pathway in AML (Zhe et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that anthracyclines, including DOX, a type of important component of current cancer treatment, generate high levels of ROS and cause severe chemotherapy-associated cardiotoxicity ( 77 79 ). Therefore, combinations of antioxidants and chemotherapeutic agents perhaps have promising synergistic effects ( 80 ). The role of OS in DOX-induced cardiotoxicity can be attenuated in a transgenic mouse model containing high levels of cardiac metallothionein, a potent antioxidant ( 81 ).…”
Section: Association Between Os and Chemotherapy During Leukemia Treamentioning
confidence: 99%